Trends in antipsychotic use among children and adolescents in Germany: a study using 2011–2020 nationwide outpatient claims data - Dörks, Michael; Bachmann, Christian J.; Below, Maike; Hoffmann, Falk; Paschke, Lena M.; Scholle, Oliver (Frontiers in Psychiatry, 2023)
Although data about the safety and effectiveness of antipsychotic (AP) use in children and adolescents is limited, studies from various countries have observed an increase of pediatric AP use. We aimed to provide an update on trends in AP use among children and adolescents in Germany.Based on nationwide outpatient claims data from Germany, we conducted a cross-sectional study. For each year from 2011 to 2020, we determined the prevalence of AP use, defined as the proportion of children and adolescents with at least one AP dispensation. We evaluated trends in AP use by age, sex, and AP class (typical vs atypical). Additionally, we assessed trends in the specialty of AP prescribers and the frequency of psychiatric diagnoses among AP users.Results: Overall, data from more than 12 million children and adolescents were included for each calendar